Оцінка взаємозв’язку людського розвитку та конкурентоспроможності на міжнародному рівні: рейтинговий аналіз - Антонюк, В.П.; Прогнімак, О.Д.; Кузнецова, Д.В. (Економіка промисловості, 2013)
Статтю присвячено аналізу взаємозв’язку людського розвитку та конкурентоспроможності України в міжнародному порівнянні, його обґрунтуванні та визначенні відповідних умов для активізації людського чинника. Відсутність ефективної взаємодії науки, освіти, бізнесу, інституціональної системи є гальмом у досягненні високого рівня конкурентоспроможності країни. Дослідження визначило потребу у формуванні національного вектору розвитку освітнього, професійного, креативного потенціалу суспільства, що буде виступати головним чинником конкурентоспроможності.
Ключові слова: людський розвиток, людський потенціал, конкурентоспроможність, економіч¬ний розвиток Статья посвящена анализу взаимосвязи человеческого развития и конкурентоспособности Украины в международном сравнении, его обосновании и определении соответствующих условий для активизации человеческого фактора. Отсутствие эффективного взаимодействия науки, образования, бизнеса, институциональной системы является тормозом в достижении высокого уровня конкурентоспособности страны. Исследование определило потребность в формировании национального вектора развития образовательного, профессионального, креативного потенциала общества, что будет выступать главным фактором конкурентоспособности.
Ключевые слова: человеческое развитие, человеческий потенциал, конкурентоспособность, экономическое развитие. In the era of globalization of economic life the important task of every country is to ensure the growth of competitiveness of the national economy. It provides not only the access to markets, resources and goods, possibility of growth of scope and efficiency of production, but also the receiving incomes and improvement the level and quality of life of population.
Modern studies show that there is a close correlation between human development and competitiveness. The development of human potential, which includes demographic, educational, socio-economic and socio-cultural components, creates social-humanitarian foundations of competitiveness. The improvement of demographic parameters and condition of population’s health provides the increasing of the number of economical active population and employed in the public sector. The strengthening of health contributes to the increase of physical endurance in the working process and work capacity. This increases the number of manpower necessary for economic development. However, the educational and socio-cultural component has the greatest influence on parameters of competitiveness.
The article is devoted to the analysis of interaction of human development and Ukraine’s competitiveness in international comparison, its justification and definition of appropriate conditions for the human factor activation. Lack of effective interaction between science, education, business, institutional system is the obstacle in achieving a high level of competitiveness of the country. The paper identifies a need in formation of the national vector development of the educational, professional, creative potential of the society, which will be the main factor of competitiveness.
Keywords: human development, human potential, competitiveness, economic development.